Protease purification from Bacillus amyloliquefaciens B7 using Aqueous Two-Phase System (ATPS) - Abd Samad, Nadiah Syuhada; Amid, Azura; Jimat, Dzun Noraini; Ab Shukor, Nurul Aqilah (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Bacillus amyloliquefaciens B7 was isolated from the fermented fish sauce and identified as protease producer. Generally, in downstream processing, purification of enzymes consumes higher cost regarding reagents and equipment used. Moreover, harsh purification methods used might cause denaturation of the enzymes. Therefore, there is a high demand for efficient and low-cost extraction and purification methods. Aqueous two-phase system (ATPS) is an alternative method that should be considered as it is simple, rapid separation yet cause little denaturation. Protease produced by B. amyloliquefaciens B7 was partitioned using two different ATPS, which were PEG/potassium phosphate and PEG/sodium citrate. Results showed the highest enzyme activity was found in interface phase with the ATPS system of 27% (w/w) PEG1500/ 34% (w/w) sodium citrate. Later, the ATPS conditions (pH, temperature, the concentration of selected salt and PEG) were optimized by using response surface methodology. The optimum conditions for ATPS purification were observed in ATPS conditions at pH 7 and 35°C with the enzyme activity of 0.20± 0.01 U/ml.